The Effectiveness of Health Education on Healthy Pregnancy Planning for Women of Childbearing Age in Olat Rarang Hamlet, Labuhan Village, Sumbawa - Fitri Setianingsih; Ninik Wahyuni; Galuh Permatasari; Evi Gustia Kesuma; Lina Eta Safitri (International Journal Of Health Science, 2026)
Maternal and child health is a fundamental parameter of a nation’s welfare. Efforts to produce a quality generation must be initiated from the pre-conception phase, long before the birth process occurs. Based on WHO recommendations (2023), pre-conception care is crucial to optimize maternal health and reduce the risk of pregnancy complications. However, in reality, pregnancy readiness is often not a priority. This study aims to analyze the effectiveness of health education on the level of knowledge of healthy pregnancy planning among women of childbearing age (WUS) in Olatrarang Hamlet, Labuhan Village, Sumbawa. The research method used a pre-experimental design with a one-group pretest-posttest approach to 30 respondents selected through a purposive sampling technique. The research instrument was a structured questionnaire, and data were analyzed using a paired t-test. The results showed a statistically significant increase in knowledge scores, from an average value of 52.43 in the pre-test to 88.67 in the post-test (p-value = 0.000). Post-intervention, the majority of respondents (86.7%) achieved the "Good" knowledge category. These findings indicate that interactive, community-based health education programs are effective in improving reproductive health literacy in rural areas.